Ameliorative effect of cheqianzi decoction on hyperuricemia and kidney injury and underlying mechanism in rats. Issue 4 (April 2023) - Meng, Jing; Tian, Jingzhuo; Zhao, Yong; Li, Chunying; Yi, Yan; Zhang, Yushi; Han, Jiayin; Wang, Lianmei; Pan, Chen; Liu, Suyan; Liu, Chenyue; Wang, Fang; et al.
Abstract: Cheqianzi Decoction (CQD) is a Traditional Chinese Medicine (TCM) formula comprising four herbs and is recorded in the Ancient Materia Medica "Shengji Zonglu". Individually, these four herbs have been shown to reduce uric acid (UA) levels, to treat hyperuricemia (HUA), and alleviate kidney damage. However, the therapeutic efficacy of the CQD and related mechanism are not yet clear. In this study, high performance liquid chromatography (HPLC) analysis confirmed that the contents of the chemical components of the four herbal medicines were in accordance with the provisions of the Chinese Pharmacopoeia. A total of 99 potential targets were identified in the network pharmacology analysis of CQD, indicating its involvement in the regulation of inflammatory and apoptotic signaling pathways, and potential value for treating HUA and alleviating kidney injury. In vivo pharmacodynamic studies showed that compared with the Model group, significantly decreased levels of serum uric acid (SUA), serum creatinine (SCr), blood urea nitrogen (BUN) (all P < 0.05), and inflammatory factors ( P < 0.01) were detected in the CQD group. Quantitative real-time PCR and Western blot analyses showed that compared with the Model group, adenosine triphosphate (ATP)-binding cassette efflux transporter G2 (ABCG2) expression in the CQD group was significantly upregulated ( P  < 0.01) at both the mRNA and protein levels, while mRNA expression of Caspase3 and NOD-like receptor family member 3 (NLRP3) ( P < 0.05) and protein expression of NLRP3 ( P  < 0.01) were significantly downregulated. In conclusion, CQD promotes UA excretion by activating ABCG2, and induces inflammasome NLRP3-mediated reduction in inflammatory and apoptotic factors to achieve renal protection. Thus, our findings indicate the therapeutic potential of CQD in HUA with kidney injury. Highlights: CQD may have therapeutic effect on hyperuricemia with kidney injury. CQD reduces uric acid by acting on ABCG2 transporter to promote uric acid excretion. CQD inhibits NLRP3 inflammasome, reduces inflammatory factors to produce anti-inflammatory effects, and alleviates kidney injury. Network pharmacology is suitable for exploring the mechanism of TCM compounds.